The Relationship Between Gender and BMI on the Pattern and Height of Pedic Arches - Hindun Saadah; Gita Aulia Sigit Putri; Sony Ramdhani; Hikmat rudyana (Sean Institute, 2026)
The arcus pedis is composed of bones that form an angle on the sole which acts as a support for body weight and a vibration absorber when the foot contact with a surface. There can be abnormalities of the arch pedis, such as flat foot and cavus foot, as well as pronation and supination. These abnormalities can be caused by genetics, obesity, trauma, and footwear habits. This study aims to determine the relationship between gender and BMI with the pattern and height of the arch of the pedis in Faculty of Medicine Unjani students class of 2021. The study was conducted on 30 students who fulfilled the inclusion criteria. The implementation of this study was in December 2023. This research method is an analytical observational conducted with a cross-sectional approach. This study used the Clarke's Angle method to identify the pedic arch pattern and the Navicular Drop Test to determine the height of the pedic arch. The results of the study were then analysed using the Chi-square test which then showed that there was a significant relationship in BMI to the arch pattern with p = 0.001 (p<0.05) and arch height with p = 0.027 (p<0.05). However, there was no significant correlation between gender and arch pattern with p = 0.749 (p>0.05) and arch height with p = 0.921 (p>0.05). This means that BMI has a role in changing the pattern and height of the pedic arch, but there is no significant effect of gender differences.